Loss of monomorphic and polymorphic HLA antigens in metastatic breast and colon carcinoma. - Goepel, J. R. (Nature Publishing Group, 1991)
MHC class I antigens are intimately involved in intercellular communication, and recognition by cytotoxic T cells. Thus tumour cells that fail to express them may be at a growth or metastatic advantage. A series of ten colorectal and ten breast carcinomas, and their respective lymph node metastases, were examined immunohistologically using monoclonal antibodies (mAb) against both monomorphic and A2 polymorphic determinants, and beta-2-microglobulin (beta 2m). Four colon polypoid adenomas stained positively throughout, but 6/10 primary tumours had partial or complete loss of expression of monomorphic determinants using mAb W6/32: two node and the liver metastasis showed less, four more expression. Similar results were seen for beta 2m. HLA-A2 expression was absent or reduced in 4/4 colon tumours and all their metastases. Among the breast tumours, W6/32 staining was absent or reduced in 2/10, and node deposits showed two with less reactivity than their primary. Beta 2m staining was reduced or absent in 8/10 primaries and all the node metastases; in every case in which beta 2m was detected in the primary tumour their corresponding lymph node metastasis showed a decreased expression. HLA-A2 expression was absent or reduced in 3/4 primary breast carcinomas, and all their metastases. These results show that individual human colon and breast carcinomas often have a reduced HLA class I antigen expression, which apparently confers a metastatic advantage. IMAGES: